Analysis of nutrient status, growth and yield parameters of Mulberry plants growing in different mandals of Anantapur district - Madhavi, R,; Vijaya Kumari, N, (The Bioscan, 2024)
The present study was conducted to determine nutrient/fertility status of the soils were derived to analysed based on the Parkers Nutrient Index and the computed index stated that the Phosphorus and potassium were at medium and high levels, besides the OC and Nitrogen being at the low and medium levels. Though variations occur in the concentration of the soil attributes, the yield attributes obtained were seen optimal for all of the monitoring sites. This is particularly crucial in precision agriculture, where understanding variations in soil properties across a field is essential for optimizing resource use, such as fertilizer application. The geostatistical procedures, management zone delineations can be facilitated and site-specific fertilizer application can be recommended. Objectives of the study: Studying the soil fertility status of mulberry growing areas in Anantapur districts is essential for several reasons: 1. Optimizing Silk Production: Mulberry plant health directly affects silk quality and yield. Understanding soil fertility and yield helps in optimizing growth conditions. 2. Nutrient Management: Identifying nutrient deficiencies allows for precise fertilizer application, improving soil health and plant productivity.